2017
DOI: 10.1080/21505594.2017.1330240
|View full text |Cite
|
Sign up to set email alerts
|

The distinct function of Tep2 and Tep6 in the immune defense of Drosophila melanogaster against the pathogen Photorhabdus

Abstract: Previous and recent investigations on the innate immune response of Drosophila have identified certain mechanisms that promote pathogen elimination. However, the function of Thioester-containing proteins (TEPs) in the fly still remains elusive. Recently we have shown the contribution of TEP4 in the antibacterial immune defense of Drosophila against non-pathogenic E. coli, and the pathogens Photorhabdus luminescens and P. asymbiotica. Here we studied the function of Tep genes in both humoral and cellular immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 80 publications
2
36
0
Order By: Relevance
“…The deletion of four Drosophila Teps did not render the flies susceptible to infection with non-pathogenic Gram-negative bacteria [55]. Tep2 has been reported to be required for the uptake of E. coli, a Gram-negative bacterium, by cultured S2 cells [48], a finding confirmed in vivo [49]. In contrast, we find no involvement of Tep2 in our in vivo intestinal infection model with P. aeruginosa, at least in terms of virulence, but do detect a requirement for Tep4 in phagocytosis and opsonization assays.…”
Section: Rhlr Counteracts the Cellular Host Defense By Eluding Detectmentioning
confidence: 83%
See 2 more Smart Citations
“…The deletion of four Drosophila Teps did not render the flies susceptible to infection with non-pathogenic Gram-negative bacteria [55]. Tep2 has been reported to be required for the uptake of E. coli, a Gram-negative bacterium, by cultured S2 cells [48], a finding confirmed in vivo [49]. In contrast, we find no involvement of Tep2 in our in vivo intestinal infection model with P. aeruginosa, at least in terms of virulence, but do detect a requirement for Tep4 in phagocytosis and opsonization assays.…”
Section: Rhlr Counteracts the Cellular Host Defense By Eluding Detectmentioning
confidence: 83%
“…The expression patterns of Tep1‐4 have been documented by in situ hybridization . The exact function of each Tep in host defense remains poorly understood despite several studies and their potential role as opsonins has not been definitely determined . Although an initial study failed to reveal a role of Tep1 , Tep2 , Tep3 , or Tep4 in several infection models, even when Tep2‐Tep3‐Tep4 triple mutants were assayed , a quadruple Tep1‐Tep2‐Tep3‐Tep4 mutant was reported to be sensitive to some fungal and Gram‐positive bacterial infections, likely because Toll pathway activation is impaired in this quadruple mutant .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial information on the function of TEPs in Anopheles mosquitoes has been acquired, but only a few studies have examined the contribution of TEPs to the antimicrobial immune response of Drosophila (11,(29)(30)(31)(32)(33)(34). Recently, we reported that Tep2, Tep4, and Tep6 in Drosophila are transcriptionally upregulated after infection with Photorhabdus luminescens or Photorhabdus asymbiotica (11,35,36). In particular, the inactivation of Tep2, Tep4, and Tep6 in Drosophila prolongs the survival of the mutants in response to Photorhabdus infection, which is accompanied by a lower level of persistence of the pathogens in infected flies.…”
mentioning
confidence: 99%
“…Of note is the significant up‐regulation of Gmm_TEP4 (MCR), especially in the salivary glands, of T. brucei ‐infected flies. In D. melanogaster , the MCR has been shown to have multiple roles in innate immunity (Stroschein‐Stevenson et al ., ; Shokal et al ., ) and in the formation and maintenance of the septate junctions (Batz et al ., ; Hall et al ., ). In T. brucei ‐infected salivary glands, the parasites tightly attach with their flagellum to the epithelial lining (Vickerman et al ., ), thereby possibly damaging the septate junctions.…”
Section: Discussionmentioning
confidence: 99%